x - меньшее основание
2x - большее основание
x + 6 - сторона
Составим уравнение:
x + 2x + 2 * (x + 6) = 60
x + 2x + 2x + 12 = 60
5x = 60 - 12
5x = 48
x = 48 / 5
x = 9,6(см.) - меньшее основание
9,6 * 2 = 19,2(см.) - большее основание
9,6 + 6 = 15,6(см) - сторона
ответ: 9,6см.;19,2см.;15,6см.;15,6см.
x - меньшее основание
2x - большее основание
x + 6 - сторона
Составим уравнение:
x + 2x + 2 * (x + 6) = 60
x + 2x + 2x + 12 = 60
5x = 60 - 12
5x = 48
x = 48 / 5
x = 9,6(см.) - меньшее основание
9,6 * 2 = 19,2(см.) - большее основание
9,6 + 6 = 15,6(см) - сторона
ответ: 9,6см.;19,2см.;15,6см.;15,6см.